2021
DOI: 10.3390/molecules26082352
|View full text |Cite
|
Sign up to set email alerts
|

A Metal-Based Receptor for Selective Coordination and Fluorescent Sensing of Chloride

Abstract: A scorpionate Zn2+ complex, constituted by a macrocyclic pyridinophane core attached to a pendant arm containing a fluorescent pyridyl-oxadiazole-phenyl unit (PyPD), has been shown to selectively recognize chloride anions, giving rise to changes in fluorescence emission that are clearly visible under a 365 nm UV lamp. This recognition event has been studied by means of absorption, fluorescence, and NMR spectroscopy, and it involves the intramolecular displacement of the PyPD unit by chloride anions. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…More recently, Formica et al reported an aza-scorpiand ligand having a pendant arm functionalized with a fluorescent pyridyl-oxadiazole-phenyl moiety (51) [70,71]. The Zn(II) complex of 51 interacts selectively with a chloride anion, which displaces the pyridine of the pyridyl-oxadiazole-phenyl moiety from the coordination sphere, generating a quenching of the fluorescence emission.…”
Section: Inclán Et Al Developed Anthracene Analogous Ligands Containing a Pyridine Moiety As An Aromatic Spacermentioning
confidence: 99%
“…More recently, Formica et al reported an aza-scorpiand ligand having a pendant arm functionalized with a fluorescent pyridyl-oxadiazole-phenyl moiety (51) [70,71]. The Zn(II) complex of 51 interacts selectively with a chloride anion, which displaces the pyridine of the pyridyl-oxadiazole-phenyl moiety from the coordination sphere, generating a quenching of the fluorescence emission.…”
Section: Inclán Et Al Developed Anthracene Analogous Ligands Containing a Pyridine Moiety As An Aromatic Spacermentioning
confidence: 99%
“…In water, anion recognition is an even more tough goal, due the hydration of both receptor and substrate, that hampers their mutual interaction. [15][16][17][18] Both free ligands [19][20][21][22][23][24][25][26][27][28][29][30][31][32] and metal complexes [33][34][35][36][37][38][39][40][41] can be employed as receptors for anions. The use of free ligands implies the formation of noncovalent interactions, such as hydrogen bonds or π-stacking, whereas the metal centers of complexes can act as binding sites for the carboxylate moieties of anionic guests, 42 also offering the receptor a structural organization ( preorganization).…”
Section: Introductionmentioning
confidence: 99%